PERAN MEDITASI DALAM MENGURANGI STRES PADA MAHASISWA SEMESTER AKHIR - Ni Luh Pitya Ulansari; I Gusti Made Widya Sena (Guna Widya: Jurnal Pendidikan Hindu, 2020)
A student in the final semester does not rule out that it will be pressure in itself for all students, because they are always required to do their best. As a final semester student, of course a lot of pressure made him stressful. This is what often happens to final semester students who are always overwhelmed by excessive worry. It is at this time that the student will experience anxiety which causes him to become stressed so that it can cause depression in the student, social deviations to suicide as a solution. The technique used is document study with data analysis using data reduction, data display and data verification in accordance with the theme that the author adopted. The purpose of this journal article is to illustrate that the stress level of final students can be reduced by doing meditation (dhyana). Various literature and research shows that through meditation (dhyana) can provide a good mood for the mental so that it affects the psyche and can reduce student stress. In this journal it was found that dhyana played a role in reducing stress levels in final semester students. The goal of meditation is to have a calm and psychically balanced mind. Of course, this can help students complete their final assignments